Transcending new public management the transformation of public sector reforms - Christensen, Tom 1949-; Lægreid, Per (Routledge, 2016)
Following on from the success of the editors' previous book, New Public Management: The Transformation of Ideas and Practice, which examined the public reform process up to the end of the last decade, this new volume draws on the previous knowledge both theoretically and empirically. It examines and debates the post-new public management reform development in Denmark, Norway, Sweden, Australia and New Zealand. The ideal follow-up to the previous volume, this book includes many of the same contributors in addition to some fresh voices, and is a must for anyone looking for an integrated framework of analysis. Comprehensive and analytical, it is an important contribution to the study of public administration and particularly to the reform of public management.